The differences in anthropometric variables and in the body composition between 7 and 8-year-olds with scoliotic changes - Wilczyński, Jacek; Karolak, Przemysław; Karolak, Joanna; Grzanka, Katarzyna; Wilczyński, Igor (Journal of Education, Health and Sport, 2018)
The aim of the study was to determine the differences between the anthropometric variables and body composition between 7 and 8-year-olds with scoliotic changes. The shape of the spine was assessed using optoelectronic Diers formetric III 4D. Body composition was assessed by a bioelectrical impedance. The study was conducted between November 2016 and July 2017 in Posture Laboratory at the Faculty of Medicine and Health Sciences UJK in Kielce. The largest absolute value of variation in 7-year-olds from scoliosis occurred for a variable BMR (kJ) (S = 598.5), the same group of posture in idiopathic scoliosis BMR (kJ) (S = 425) and standard BMR (kJ) (S = 666). In 8-year-olds in the group of scoliosis the differences were also observed in the largest absolute value of the variable BMR (kJ) (S = 639) and in the attitudes scoliotic group (S = 602) and standard (S = 483). The univariate analysis of variance showed significant differences between 7 and 8 year-olds in the group of scoliosis in the measurement of body height (cm), weight (kg), FFM (kg) of muscle mass (kg) TBW (kg), BMR (kJ), BMR (kcal), bone mass (kg) and protein (kg) (p <0.05). In the scoliotic group attitudes significant differences occurred in the body height (cm) weight (kg) BMI, fat mass (kg), FFM (kg) and muscle mass (kg) TBW (kg), BMR (kJ) BMR (kcal), bone weight (kg) and the amount of protein (kg) (p <0.05).